Prosthetic encounter and queer intersubjectivity in The Merchant of Venice. Issue 7 (9th November 2016) - Hobgood, Allison P.
ABSTRACT: This essay is about queer rings in Shakespeare's The Merchant of Venice . Troubling readings of the ring scenes in the play's critical history, this essay employs object-oriented theories to situate prosthetic matter within an inherently queer phenomenology. It explores the ways that prosthetic non-self matter cultivates transformative interchanges between people and even other things, and thus argues for prostheses as the basic material of intersubjective exchange and emotional encounter between bodies in the world. Merchant's rings showcase how (dis)orienting prosthetic materials extend and reshape the psychic landscapes and embodied experiences of those who come into contact with them. They are lively, familiar matter that, paradoxically, produces new, unfamiliar orientations. They expose the highly contingent social interfaces between 'selves' and 'others, ' and also illuminate the queer potentiality of complex, precarious assemblages made possible through prostheses.